2000
DOI: 10.1021/ic990520z
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Two High-Affinity Hexamer Peptides to Copper(II) and Palladium(II) Models of the Peptide−Metal Chelation Site on IMAC Resins

Abstract: The coordination of peptides Ser-Pro-His-His-Gly-Gly (SPHHGG) and (His)6 (HHHHHH) to [PdII(mida)(D2O)] (mida2- = N-methyliminodiacetate) was studied by 1H NMR as model reactions for CuII(iminodiacetate)-immobilized metal affinity chromatography (IMAC) sites. This is the first direct physical description of peptide coordination for IMAC. A three-site coordination is observed which involves the first, third, and fourth residues along the peptide chain. The presence of proline in position 2 of SPHHGG achieves the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The large separation of pK 101 and pK [1][2][3][4][5][6][7][8][9][10][11] , and the small change in the Vis, CD and EPR spectra of the CuH À2 L species compared to [CuH À1 L] + indicates the formation of a mixed hydroxo ligand complex with {N im , N À amide , N im , OH À ) type coordination (Scheme 1). The pK 1-11 for the [CuH À1 L] + = CuH À1 L(OH) + H + process is 8.26, that is one unit lower, than e.g.…”
Section: Copper(ii) Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The large separation of pK 101 and pK [1][2][3][4][5][6][7][8][9][10][11] , and the small change in the Vis, CD and EPR spectra of the CuH À2 L species compared to [CuH À1 L] + indicates the formation of a mixed hydroxo ligand complex with {N im , N À amide , N im , OH À ) type coordination (Scheme 1). The pK 1-11 for the [CuH À1 L] + = CuH À1 L(OH) + H + process is 8.26, that is one unit lower, than e.g.…”
Section: Copper(ii) Complexesmentioning
confidence: 99%
“…doi:10.1016/j.jinorgbio.2008.01.006 their surface [5][6][7]. Moreover, H and H/P-rich sequences like hexahistidine or GHPHHG have been playing important role in anchoring and purifying proteins on metal ionaffinity chromatography [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A commonly used IMAC column has Cu II , Ni II , or Zn II sites supported by iminodiacetate chelation that is attached to a resin support (1)(2)(3). [Pd II (mida)(peptide)] complexes, mida 2-) N-methyliminodiacetate, have been useful for NMR purposes in modeling the coordination of peptides to IMAC binding sites (9,10). It was shown that the carboxylate donors from the mida 2-portion of the molecule are displaced as the peptide chain establishes a three-point contact via the remaining square-planar coordination positions of the Pd II center as shown in the figure for the Ser-Pro-His-His-Gly-Gly peptide (SPH-HGG) (9).…”
Section: Introductionmentioning
confidence: 99%
“…[Pd II (mida)(peptide)] complexes, mida 2-) N-methyliminodiacetate, have been useful for NMR purposes in modeling the coordination of peptides to IMAC binding sites (9,10). It was shown that the carboxylate donors from the mida 2-portion of the molecule are displaced as the peptide chain establishes a three-point contact via the remaining square-planar coordination positions of the Pd II center as shown in the figure for the Ser-Pro-His-His-Gly-Gly peptide (SPH-HGG) (9). EPR spectra of the Cu II analogue, [Cu II (mida)-(peptide)], confirm a similar structure for the Cu II -ida IMAC site models (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation